1995
DOI: 10.1002/adma.19950070204
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel processing of optical and electrooptical materials

Abstract: The sol–gel process represents a room‐temperature method of producing a wide range of ceramic materials through the formation of a glassy network by the polymerization of suitable monomers. The use of the technique to produce, for example, sonogels, organic‐inorganic composites, NLO glasses, and electrooptical materials such as gel‐glass dispersed liquid crystald (GDLCs) is reviewed. An example of a GDLC is shown on this issue's front cover, 4‐pentyl‐4‐biphenylcarbonitrile in the LC state being dispersed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(73 citation statements)
references
References 59 publications
1
71
0
1
Order By: Relevance
“…To investigate these possibilities, we have originated a study of silica sonogels as possible hosts for VOz nanocrystals. Sonogels were preferred over conventional gels because of their short gelation time and their excellent properties as a host matrix for nanoparticles [17]. One possible way of making such a SiOflO2 composite is an "in situ" impregnation, where that the V~O S sol can be directly used as one of the compounds to make the sonogel.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate these possibilities, we have originated a study of silica sonogels as possible hosts for VOz nanocrystals. Sonogels were preferred over conventional gels because of their short gelation time and their excellent properties as a host matrix for nanoparticles [17]. One possible way of making such a SiOflO2 composite is an "in situ" impregnation, where that the V~O S sol can be directly used as one of the compounds to make the sonogel.…”
Section: Methodsmentioning
confidence: 99%
“…Organic compounds, particularly volatile ones such as pheromones, rarely survive temperatures above 200°C during such processes. Levy and Esquivias (1995) reported that incorporation of organic dyes into sol-gels and drying, even at temperatures below 150°C, resulted in cracking, shrinkage and high porosity, which facilitated the leaching of the small molecules. Moreover, it is likely that some of the pheromone was trapped within cavities in the matrix that are accessible only through micropores, through which the pheromone molecules were too large to pass.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy examples include self-assembled monolayers and superlattices (Yitzchaik and Marks, 1996), sol-gel silica glasses (Levy and Esquivias, 1995), and biomaterials (Gallot et al, 1996;Willner and Rubin, 1996;Sisido et al, 1991a). A number of small molecules incorporating azobenzene have been synthesized, including crown ethers (Shinkai et al, 1983), cyclodextrins (Jung et al, 1996;Yamamura et al, 1996), proteins such as bacteriorhodopsin (Singh et al, 1996), and three-dimensional (3-D) polycyclics such as cubane (Chen et al, 1997b) and adamantane (Chen et al, 1995).…”
Section: Classes Of Azobenzene Systemsmentioning
confidence: 99%